Kreativitas Guru dalam Mengembangkan Media Pembelajaran DIY (Do It Yourself) pada Mata Pelajaran Fiqih di MI NU Kota Metro - Lutfi Fadilah (CV. Creative Tugu Pena, 2024)
The main problem in this research is limited resources and facilities to create innovative and interesting learning media. This research aims to examine the creativity of teachers at MI NU Metro City in designing DIY learning media for Fiqh subjects, as well as evaluating the effectiveness of this media in increasing students' understanding and involvement during the teaching and learning process. The method used is qualitative research with a case study approach, which aims to explore and understand social phenomena in a particular context through in-depth and comprehensive analysis. The results of this research show that teachers are able to develop various forms of creative and effective learning media, such as visual aids, educational cards, educational games, and DIY projects. The use of DIY media has proven to be effective in significantly improving student learning outcomes, both in terms of achieving test scores and students' ability to apply Fiqh concepts in everyday life.